A Study on how primetime weekday TV programs influence the lifestyle of Filipino college students - Bautista, Hannah Victoria A.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
The study attempted to answer how primetime weekday programs influence the culture, lifestyle of Filipino college students. The study answered the problem by focusing on three broad aspects. First is the history if Philippine TV programming, more specifically to ascertain what types of programs have appealed to Filipinos and how the influx of imported programs affect the Filipino viewers program preferences as well as the type of shows to be exhibited. Second is audience analysis, particularly the television viewing habits of Filipino viewers and how this relates to the influences of the television. And finally, program analysis, which focuses on the content (i.e., program genre, theme, language and the like) of the top three shows viewed in the primetime slot. Key-informant interviews were conducted with the programming executives of channels 2, 7, and 23. These were conducted to 1) give a brief background on Philippine TV, 2) establish the trends in programming and 3) ascertain how the influx of imported programs influence local shows. A survey with two hundred (200) respondents was conducted in selected schools in Manila to represent a cross-section of all income levels to establish the behavioral pattern of students watching TV and to asses the latter's impact on the students way of life. In addition, a textual analysis of the top ranking programs was conducted to determine the content of the shows as well as the different mechanics of the top rated programs because it is assumed that these programs have the greatest impact on the respondents. The findings of the study are the respondents watch TV at an average of 6 hours, everyday during weekdays while engaging in some other form of activity. Their favorite programs are TV Patrol, Ghostfighter, and Ally McBeal. Television has a very high influence in terms of the aspect of information, acquiring knowledge on the latest fads and the type of food and consumer products brought. The degree of concentration that the respondents have while watching TV has an influence on the lifestyle of Filipino college students such as obtaining information, making decisions, scheduling ones time, buying behavior, etc. Gender and income have an influence on program choice as well as the number of hours devoted to watching TV. Males prefer to watch programs as Ghostfighter, Flame of Recca, and PBA while females like TV Patrol, Ally McBeal and Dawson's Creek and Charmed. Those with high income prefer Dawson's Creek, TV Patrol and Charmed while those with low income like Ghostfighter, TV Patrol and MTV.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Youth television programs -- Philippines